2020
DOI: 10.21109/kesmas.v15i2.3950
|View full text |Cite
|
Sign up to set email alerts
|

Pre-testing of the WHO’s Educational Video: “How to Protect Yourself Against COVID-19”

Abstract: The coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was declared a public health emergency in many countries, including Indonesia. The World Health Organization (WHO) released an educational video, entitled "How to Protect Yourself Against COVID-19", which explained how to prevent the spread of COVID-19. This study is a qualitative study that aims to pre-test this video, based on the Information, Education, Communication (IEC) theory, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In another study by Fadliyah et al (2020), about pre-testing educational videos by WHO on the prevention of COVID-19 transmission, participants found the video contents to fit their values, with the portrayed message addressing all the different groups of the community. The participants had positive perceptions of the video since it was considered persuasive to the population (Fadliyah et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In another study by Fadliyah et al (2020), about pre-testing educational videos by WHO on the prevention of COVID-19 transmission, participants found the video contents to fit their values, with the portrayed message addressing all the different groups of the community. The participants had positive perceptions of the video since it was considered persuasive to the population (Fadliyah et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…A study observed that in a Pre-testing campaign about safe sex in a television advertisement; where a storyboard with images and text presented to members of a target population of students (between 14 and 16 years) enrolled in a vocational school showed results of a positive effect on safe sexual behavior (Whittingham et al, 2008). In another study by Fadliyah et al (2020), about pre-testing educational videos by WHO on the prevention of COVID-19 transmission, participants found the video contents to fit their values, with the portrayed message addressing all the different groups of the community. The participants had positive perceptions of the video since it was considered persuasive to the population (Fadliyah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the time when WHO declared the novel coronavirus disease (COVID-19) pandemic in March 2020, all levels of society are facing new lifestyle changes. [ 16 ] The prevalence of anxiety and depression in perinatal mothers has significantly increased after the spread of COVID-19 throughout the world. [ 17 ] Isolation, wearing a mask, social distancing, frequent handwash, new public policies, changes in perinatal health care, fear of COVID-19 exposure, and shortage of health workers due to COVID-19 infection can increase the extreme stress experienced by mothers.…”
Section: Introductionmentioning
confidence: 99%